The Investment of Sharia Shares in Indonesia Stock Exchange Representative in Sharia Law Economic Perspective - Itsna Nur Muflikha; Sya'roni Sya'roni; Abdualhmeed Alqahoom; Setya Pramana (Walidem Institute and Publishing (WIP), 2023)
Investment and the sale and purchase of shares are still considered speculative activity and is prohibited by religion because it is the same as gambling for ordinary people. To straighten this out, this study aims to analyze how Islamic stock investment in the Indonesia Stock Exchange from the perspective of Islamic economic law. The research method used is normative juridical with a qualitative approach. This research draws research sources from interviews with several investors and Sharia economic law experts, then documents of laws and regulations, and literature studies related to research. The results show that investing and buying and selling of shares is halal and justified in the teachings of Islam, both Al-Qur'an, the Prophet's Hadith, Kaidah Fiqh, Ijma 'ulama, and the opinions of scholars. Then, from the perspective of Sharia economic law, buying and selling or investing in shares for investment purposes is permitted, because buying and selling with underlying stocks is halal, even recommended because it fulfils investment and asset development of one of the maqasid sharia (Hifdzul maal). In addition, stock transactions from the perspective of Sharia economic law are assessed from the use of the contract. It is known that the contract used is Bai 'Al-Musawamah and the transaction refers to musyarakah or syirkah.